Vacíos en la legislación de obras por impuestos a partir de su aplicación práctica - Zúñiga Aleman, Laura (2014)
The Public Works Tax Deduction Law has been enacted to foster public investment at a local and regional level by including participation from the private sector and through the subscription of agreements with local and regional governments.Nonetheless its noble purposes, in the application field of the Law, normative gaps are put into evidence, which impede its practical application. In the present article, the author shows which are the Law’s deficiencies, while analyzing them and proposing possible solutions.